Libraries as Dysfunctional Organizations and Workplaces - Acadia, Spencer (Milton Park, Abingdon, Oxon: New York, NY: Routledge, 2023)
"Libraries as Dysfunctional Organizations and Workplaces expands the 'dysfunctional' concept in the professional and academic LIS discourse by exposing the internal problematics of libraries, especially at the social and organizational level. Including contributions written by LIS professionals and scholars, the book demonstrates that although many libraries do well at attending to users and managing external information they often fail at taking care of their own employees and addressing internal workplace issues. Acadia and the contributing authors explore the problem of dysfunctional libraries so that the LIS profession can come to terms with the systemic dysfunction in their institutions and begin solution-oriented and change-positive progress toward new and sustainable functionality. The book analyses the dysfunctional nature of modern libraries, while simultaneously proposing solutions to reduce and alleviate dysfunction. Through theory and application, it takes an explicit practice-based approach with the intent to inform and explain dysfunction as experienced in the library workplace at individual and structural levels and perspectives. Libraries as Dysfunctional Organizations and Workplaces brings the dysfunction discourse to the attention of LIS academics and scholars, so that further theoretical and empirical research can proceed from and subsequently be addressed in library and information schools. The book will also be essential reading for librarians and LIS students currently working or preparing to work in public, college, and university libraries"--
An Introduction to Dysfunction in the Library Workplace / Spencer Acadia and Kyndal Vogt -- The Dysfunctional Library and Academic Librarian Turnover / Amanda Foster Kaufman, Amy F. Fyn, Millicent Weber and Christina Heady -- Improving Dysfunctional Recruitment and Retention in Academic Libraries by Honoring the Whole Person / Erica Lopez -- Precarity Doesn't Care: Precarious Employment as a Dysfunctional Practice in Libraries / Adena Brons, Chloe Riley, Ean Henninger and Crystal Yin -- Discrimination as Dysfunction: Why do Libraries Have a Problem with Diversity, Equity, and Inclusion? / Briana Zaragoza and T. Gonzalez -- Workplace Dysfunction and Intellectual Freedom in Public Libraries / Miranda Doran-Myers and Crystal Schimpf -- The Saboteur in the Academic Library / Kate Dohe, Celia Emmelhainz, Maura Seale and Erin Pappas -- 'Put the Fucking Salary in the Job Ad!': An Analysis of an Anonymous Corpus of Tweets / Tim Ribaric -- You are Seen: An Analysis of Library Dysfunction Found in Online Memes / Éthel Gamache and Spencer Acadia -- A Descriptive Study of Workplace Bullying in U.S. Libraries during the COVID-19 Pandemic / Carol Anne Geary and Spencer Acadia -- Work Alienation in Academic Libraries: A Marxist Analysis of Library Dysfunction / Zorian M. Sasyk -- Bamboo Ceiling Reframed: Exclusion through Social Practices and Structures in Libraries / Silvia Vong -- Combating Destruction: Organizational Power and Conflict in Academic Libraries / Sara Parme and Amy Pajewski -- Dysfunction by (Dis)organization: The Academic Library within University Structure and Organization / Jasmine Hoover.
Includes bibliographical references and index.
Keywords: Library personnel management -- United States; Library personnel management -- Canada; Communication in library administration; Library employees -- Attitudes; Libraries -- Sociological aspects; Organizational behavior; Work environment